Short term outcomes and resource utilization in de-novo versus acute on chronic heart failure related cardiogenic shock: a nationwide analysis - Quien, Mary; Bae, Ju Young; Jang, Sun-Joo; Davila, Carlos (Frontiers in Cardiovascular Medicine, 2024)
Background: There has been growing recognition of non-ischemic etiologies of cardiogenic shock (CS). To further understand this population, we aimed to investigate differences in clinical course between acute on chronic heart failure related (CHF-CS) and de-novo CS (DN-CS).Methods: Using the Nationwide Readmission Database, we examined 92,426 CS cases. Outcomes of interest included in-hospital and 30-day outcomes and use of advanced heart failure therapies.Results: Patients with DN-CS had higher in-hospital mortality than the CHF-CS cohort (32.6% vs 30.4%, p<0.001). Mechanical circulatory support (11.9% vs 8.6%, p<0.001) was more utilized in DN-CS. Renal replacement therapy (13.8% vs 15.5%, p<0.001) and right heart catheterization (16.0% vs 21.0%, p<0.001) were implemented more in the CHF-CS cohort. The CHF-CS cohort was also more likely to undergo LVAD implantation (0.4% vs 3.6%, p<0.001) and heart transplantation (0.5% vs 2.0%, p<0.001). Over the study period, advanced heart failure therapy utilization increased, but the proportion of patients receiving these interventions remained unchanged. Thirty days after index hospitalization, the CHF-CS cohort had more readmissions for heart failure (1.1% vs 2.4%, p<0.001) and all causes (14.1% vs 21.1%, p<0.001) with higher readmission mortality (1.1% vs 2.3%, p<0.001).Conclusion Our findings align with existing research, demonstrating higher in-hospital mortality in the DN-CS subgroup. After the index hospitalization, however, the CHF-CS cohort performed worse with higher all-cause readmission rate and readmission mortality. The study also underscores the need for further investigation into the underutilization of certain interventions and the observed trends in the management of these CS subgroups.